Role of Ultrasound In The Management of De’Quervain’s Disease - Hassan, Muhammad Kamrul; Rahman, M Habibur; Sobhan, Fauzia; Shoma, Farzana Khan; Walid, Chowdhury Mohammad (Medicine Today, 2013)
This prospective type of experimental study was carried out to determine the improvement of symptoms by ultrasound therapy in management of de'Quervain's disease. It was done in the department of physical medicine and rehabilitation in Dhaka medical college hospital during the period of 30th January 2008 to 30th July 2008.The diagnosis of de'Quervain's disease confirmed by history and clinical examination(Finkelstein test). 50 patients were selected and randomly divided into two groups. Group-A patients were treated with thumb splint,NSAIDS and ADL. Group-B patients were treated with thumb splint, NSAIDS, ADL and ultrasound therapy. Each patients was assessed by pain score, visual analogue scale(VAS), grading of tenderness and swelling. Mean age was 41.02 years. Female and male ratio was 7.5:1. Most patients occupation was housewife 40(80%) and had a precipitating factor as wringing of cloths 31(62%). History of recurrence was found in 7(14%). Most of the patients developed pain gradually 72%(36). Post treatment VAS score improved significantly in group B(p<0.05), in groupB 96%(24) and in group A 52%(13) patients had VAS score 0 to 4. Post treatment significantly (p<0.01) higher number of patients were in swelling score. So in group B(84%) compared to group A (44%), After treatment pain score showed significant improvement (p<0.01) in group B patients (72%) compared to group A(24%). In group A, 16%(4) and in group B 32%(8) patient were completely cured(No pain,no tenderness and no swelling). DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14112 Medicine TODAY Vol.24(1) 2012 pp.31-35